2010
DOI: 10.3109/10253891003596822
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and cardiovascular parameters during simulation of stress-induced rise in circulating oxytocin in the rat

Abstract: Physiological functions of oxytocin released during stress are not well understood. We have (1) investigated the release of oxytocin during chronic stress using two long-term stress models and (2) simulated stress-induced oxytocin secretion by chronic treatment with oxytocin via osmotic minipumps. Plasma oxytocin levels were significantly elevated in rats subjected to acute immobilization stress for 120 min, to repeated immobilization for 7 days and to combined chronic cold stress exposure for 28 days with 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…The anti-inflammatory effect of OXT may also be related to its participation in the regulation of the hypothalamic pituitary-adrenal axis. OXT potentiates the release of ACTH and the increase in corticosterone/cortisol levels [19,29,30]. In addition, OXT secretion is considered to promote insulin and glucagon secretion, and thus to regulate the peripheral metabolism during infection [27].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effect of OXT may also be related to its participation in the regulation of the hypothalamic pituitary-adrenal axis. OXT potentiates the release of ACTH and the increase in corticosterone/cortisol levels [19,29,30]. In addition, OXT secretion is considered to promote insulin and glucagon secretion, and thus to regulate the peripheral metabolism during infection [27].…”
Section: Discussionmentioning
confidence: 99%
“…Animals The immobilization (IMO) stress was conducted by gently restraining the animal in a prone position and taping its four limbs to metal mounts attached to a wooden board. This procedure was originally described by Kvetnansky and Mikulaj (1970), and it has been used in several labs (Nostramo et al, 2012;Nostramo et al, 2013;Ondrejcakova et al, 2010;Tillinger et al, 2013). In our group, the procedure has been adapted to minimize the movement of the animal and therefore the probability to induce inflammation in the paws.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Thus, increased activation of both p38-MAPK and Hsp27 protein observed in the present study may indicate involvement of these proteins in cardioprotective potential of oxytocin. Moreover, increased activation of p38-MAPK pathway may be, at least partially, responsible for oxytocin-induced increase in the heart weight without apparent enhancement of cell proliferation observed in our previous study (Ondrejcakova et al 2010). Kobayashi et al (2009) demonstrated an increase in phosphorylated ERK in the hearts of rabbits injected with oxytocin postinfarction.…”
Section: Discussionmentioning
confidence: 91%
“…Oxytocin may be considered a typical stress hormone responding to several acute and chronic stress stimuli and has a great array of physiological activities in the periphery (Jezova et al 1995;Ondrejcakova et al 2010). Cardiovascular system belongs to important targets of oxytocin action that is supported by the presence of oxytocin receptors in the heart (Gutkowska et al 1997) and vascular endothelial cells (Thibonnier et al 1999;Jankowski et al 2000).…”
Section: Introductionmentioning
confidence: 99%